Multiculturalism: Unveiling Intercultural Communicative Competence in Modern Islamic Education - Ardhy, Andi Anugrah Surya (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This research explores integrating multiculturalism and Intercultural Communicative Competence (ICC) in modern Islamic education. This research method is a qualitative study of existing literature. This research uses a literature review approach to explore the definition and dimensions of ICC, the challenges and opportunities in its integration into Islamic education, and the impact of multiculturalism on forming the Islamic education paradigm using thematic analysis of the Miles and Huberman model. Findings suggest a different understanding of ICC, which includes cultural awareness, cross-cultural sensitivity, and adaptive capacity. Despite efforts, challenges like resistance to Western influence and conceptual barriers still exist in integrating ICC into Islamic education. Promising practices, including collaborative approaches between Islamic and non-Islamic educational institutions, show potential for increased integration. Multiculturalism significantly influences educational approaches, offering opportunities to foster cross-cultural understanding and tolerance. Recommendations for future research include further exploration of effective teaching strategies, the development of inclusive learning methods, and longitudinal studies to assess the long-term impact of ICC integration in Islamic educational settings.